Socialist Churches: Heritage Preservation and "Cultic Buildings" in Leningrad, 1924-1940 - Kelly, C (2012)
The demolition of churches is a notorious episode in Soviet political history, normally discussed in the context of the history of church-state relations. Yet which prerevolutionary buildings were meant to fit into a "model socialist city" such as Leningrad and how this was to happen was also a planning issue. Soviet planners (unlike members of the militant atheist movement) drew a distinction between buildings and their (current or possible) functions. The monument protection agencies were often successful in arguing that buildings of "historic and artistic importance" should be preserved, even in the face of considerable pressure from other city departments (for example, the suggestion that Smol'nyi Cathedral be demolished for the bricks). However, they gave preference to churches that lacked an "odiously ecclesiastical appearance," were ruthless about sacrificing churches that they deemed to be of secondary significance, and readily agreed to secular uses for "cultic buildings." As Catriona Kelly shows in this article, most of the local intelligentsia considered these planning decisions to be appropriate; it was not until the postwar decades, and more particularly the Brezhnev era, that attitudes to "cultic buildings" began to change.